Theoretical approaches of political parties in public relations: analysis of modern communication models and hybrid PR concepts - Saydullayeva , Dilrabo (The Lingua Spectrum, 2026)
This article analyzes the theoretical approaches of political parties in the field of public relations (PR). In particular, it explores the essence of classical PR theory, modern communication models, and hybrid PR concepts. Based on scientific sources, the role of PR in political processes, the importance of media relations, and the transformation processes in the digital environment are examined. The results of the study serve as an important theoretical foundation for developing effective communication strategies for political parties.